2011
DOI: 10.1590/s0102-311x2011000300013
|View full text |Cite
|
Sign up to set email alerts
|

Padrões de consumo de alimentos e fatores associados em adultos de Ribeirão Preto, São Paulo, Brasil: Projeto OBEDIARP

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
29

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 33 publications
(54 reference statements)
4
27
1
29
Order By: Relevance
“…The distribution of those patterns by sociodemographic characteristics of the ELSA-Brasil study population is similar to recent findings in the Brazilian literature. Although using different methods, Gimeno et al 37 observed greater frequency of the "healthy" pattern among women and older adults, while Marchioni et al 13 and Arruda et al 38 observed higher frequencies of the traditional pattern among men and among individuals with less schooling.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of those patterns by sociodemographic characteristics of the ELSA-Brasil study population is similar to recent findings in the Brazilian literature. Although using different methods, Gimeno et al 37 observed greater frequency of the "healthy" pattern among women and older adults, while Marchioni et al 13 and Arruda et al 38 observed higher frequencies of the traditional pattern among men and among individuals with less schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, instead of assessing nutrients or food in isolation, the analysis of dietary patterns considers the combinations present in the overall diet and incorporates the complex interactions that occur among the nutrients. The dietary patterns represent a broader frame of nutrients and food consumption, thus being more appropriate for the study of dietary factors and diseases 7,8,9,10,11,12,13,14,15,16 . In order to address these questions, several authors are proposing alternatives to study the global consumption of food, considering that food is usually consumed in a combination of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Factors and the cluster analyses are the techniques most commonly used for the study of dietary patterns 8,9,10,17,18 . However, Hoffmann et al 19 have recently proposed a new statistical approach, the reduced rank regression (RRR).…”
Section: Introductionmentioning
confidence: 99%
“…Parte dessa morbimortalidade é atribuída às modificações no padrão alimentar da população, principalmente pelo aumento no consumo de calorias, gordura animal e alimentos industrializados, além de diminuição na ingestão de fibras, frutas e verduras (2,3) . Por isso, o consumo alimentar pode ser considerado um determinante da saúde, cujo caráter positivo ou negativo depende das escolhas feitas no cotidiano, quando da compra, aquisição e consumo de alimentos (4) .…”
Section: Introductionunclassified